A relação entre capacidades empáticas, depressão e ansiedade em jovens - Alves, Simone Marin (2012)
According to Martin Hoffman, empathy is an affective response oriented more to another person´s inner state than to its own. Although the development of empathic affect promotes the internalization of moral principles, it can also generate emotional costs when the anxiety aroused in the self is very intense, impairing the use of empathic capacities. It is considered that emotional overload is a vulnerability point of empathy that can lead to mood disorders such as Depression and Anxiety. This study aimed to investigate the relations and associations between empathy (Personal Distress, Empathic Concern, Fantasy and Perspective Taking), Depression and Anxiety. We intended to answer the following questions: are there significant positive associations between the scores of Empathy, Anxiety and Depression? What are the relations between empathic capacities (Personal Distress, Empathic Concern, Fantasy and Perspective Taking), Depression and Anxiety? A theoretical model of associations between variables was hypothesized and tested through a structural equation modeling (SEM) and relations between variables were checked using a multivariate analysis of variance (MANOVA). Two hundred and twenty seven volunteers (42.7% male and 57.3% female), mean age of 16.4 years (SD = 3.3), students from public and private schools of João Pessoa city took part in the study. Participants responded to the Multidimensional Scale of Interpersonal Reactivity and the Beck Scales for Depression (BDI-II) and Anxiety (BAI-II). Structural equation modeling analysis confirmed the hypothesized model, showing a positive association between Empathy and Depression, Empathy and Anxiety and Depression and Anxiety. These results revealed that a greater sensitivity to the suffering of others may predispose young people to develop Depression and Anxiety. MANOVA analyzes revealed that groups with higher Fantasy and Personal Distress presented higher scores on Anxiety. Another significant difference between groups was found for Perspective Taking and Depression, showing that the group with low Perspective Taking presented more Depression. Interaction effects analysis showed that: a) the group with high Personal Distress and low Perspective Taking presented higher scores on Depression; b) the group with high Fantasy and high Empathic Concern had greater scores on Anxiety; and c) the group with high Fantasy and low Perspective Taking had higher scores on Anxiety. From these analyzes, we concluded that the emotional costs of empathy seem to be regulated by a better use of the Perspective Taking ability, promoting the psychological wellfare and social-moral development of young people.